THE STUDY OF THE IMPLEMENTATION OF THE HOT-FIT MODEL IN ANALYZING THE USE OF QRIS IN MALANG CITY - Triyan Febriandika; Ike Kusdyah Rachmawati; Theresia Pradiani (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
This study aims to analyze the implementation of the HOT-FIT model in the use of QRIS in Malang City, focusing on the variables of System Quality, Information Quality, and Service Quality. Involving 180 QRIS users as respondents, the results indicate that user satisfaction significantly affects the benefits of using the QRIS application. Information quality has a significant impact on user satisfaction but does not directly influence benefits or system usage. Meanwhile, service quality significantly affects user satisfaction, benefits, and system usage. System quality also significantly influences user satisfaction and system usage, but does not directly affect the benefits received by users. Furthermore, system usage proves to have a significant effect on the benefits obtained. Mediation analysis shows that user satisfaction serves as a significant mediator between service quality, system quality, and benefits, whereas information quality does not show a significant impact on benefits through system usage. These findings provide important insights for the development and enhancement of QRIS services in Malang City to improve user experience and perceived benefits. This research is expected to contribute to the understanding of the factors influencing the effectiveness of QRIS usage and to offer recommendations for service providers to enhance quality and user satisfaction.